Men in eating disorder units: a service evaluation survey regarding mixed gender accommodation rules in an eating disorder setting. (26th July 2018) - Fukutomi, Akira; Connan, Frances; Winston, Anthony P.; Ghosh, Pia
Abstract : Aims and method: This service evaluation was conducted to find out: (1) if mixed gender accommodation in eating disorder units is perceived to be helpful or unhelpful for recovery, and (2) if men were being discriminated against by the implementation of the 2010 Department of Health (DoH) guidelines on the elimination of mixed gender wards. All 32 in-patient units accredited on the Quality Network for Eating Disorders were contacted via a survey. Results: We received 38 responses from professionals from 26 units and 53 responses from patients (46 female, 7 male) from 7 units. Four units had closed admissions to male patients due to DoH guidelines. Clinical implications: We found that it is possible to provide admission for men with eating disorders, while respecting the single gender accommodation rules, and that doing so is likely to be helpful for both genders and prevents discrimination against men. Declaration of interest: None.